The cinnamyl alcohol dehydrogenase gene family is involved in the response to Fusarium oxysporum in resistant and susceptible flax genotypes - R. O. Novakovskiy; L. V. Povkhova; G. S. Krasnov; T. A. Rozhmina; A. A. Zhuchenko; L. P. Kudryavtseva; E. N. Pushkova; P. Kezimana; A. V. Kudryavtseva; A. A. Dmitriev; N. V. Melnikova (Вавиловский журнал генетики и селекции)
Flax (Linum usitatissimum L.) is used for the production of textile, oils, pharmaceuticals, and composite materials. Fusarium wilt, caused by the fungus Fusarium oxysporum f. sp. lini, is a very harmful disease that reduces flax production. Flax cultivars that are resistant to Fusarium wilt have been developed, and the genes that are involved in the host response to F. oxysporum have been identified. However, the mechanisms underlying resistance to this pathogen remain unclear. In the present study, we used transcriptome sequencing data obtained from susceptible and resistant flax genotypes grown under control conditions or F. oxysporum infection. Approximately 250 million reads, generated with an Illumina NextSeq instrument, were analyzed. After filtering to exclude the F. oxysporum transcriptome, the remaining reads were mapped to the L. usitatissimum genome and quantified. Then, the expression levels of cinnamyl alcohol dehydrogenase (CAD) family genes, which are known to be involved in the response to F. oxysporum, were evaluated in resistant and susceptible flax genotypes. Expression alterations in response to the pathogen were detected for all 13 examined CAD genes. The most significant differences in expression between control and infected plants were observed for CAD1B, CAD4A, CAD5A, and CAD5B, with strong upregulation of CAD1B, CAD5A, and CAD5B and strong downregulation of CAD4A. When plants were grown under the same conditions, the expression levels were similar in all studied flax genotypes for most CAD genes, and statistically significant differences in expression between resistant and susceptible genotypes were only observed for CAD1A. Our study indicates the strong involvement of CAD genes in flax response to F. oxysporum but brings no evidence of their role as resistance gene candidates. These findings contribute to the understanding of the mechanisms underlying the response of flax to F. oxysporum infection and the role of CAD genes in stress resistance.